Participatory and Institutional Approaches to Agricultural Climate Services: A South and Southeast Asia Regional Technical & Learning Exchange - Krupnik, Timothy J.; Alam, A.; Zebiak, Stephen E.; Khanam, Fahmida; Hossain, Mohammed Khaled; Kamal, Mustafa; Miah, Azahar Ali; Shahriar, Saleh Mohammad; Khan, M. Shahidul Haque; Hussain, Sk. Ghulam (2018)
In order to share experience and boost capacity in agricultural climate services, a three-day workshop titled ‘Participatory and Institutional Approaches to Agricultural Climate Services Development: A South and South East Asia Regional Technical and Learning exchange” was held between September 17-19, 2017, in Dhaka, Bangladesh, with more than 50 leaders in agricultural climate services from 11 countries attending. The workshop was sponsored by the U.S. Agency for International Development (USAID) behalf of the Climate Services for Resilient Development (CSRD). The workshop was organized by the International Maize and Wheat Improvement Center (CIMMYT) alongside the SERVIR and Climate Services Support Activity and CSRD South Asian partners.